Edukasi Etika Batuk sebagai Kegiatan Pengabdian Masyarakat di TK Stella Maris: Membangun Perilaku Hidup Bersih dan Sehat Sejak Dini - Lontoh, susy olivia; Novendy; Irawaty, Enny (Lembaga Pengembangan Kinerja Dosen, 2025)
The application of proper cough etiquette is an essential part of Clean and Healthy Living Behavior (PHBS) and serves as a preventive measure in reducing the transmission of respiratory infectious diseases from an early age. Health education for young children is crucial, as this stage represents the formative period where foundational habits are developed, potentially influencing long-term individual and environmental health. This community service activity was conducted on May 9, 2025, at Stella Maris Kindergarten in Tangerang City, involving 29 Nursery group children. The main objective of the program was to enhance the knowledge and skills of early childhood students in practicing correct cough etiquette and to instill healthy behaviors that they can apply in their daily lives at home and school. The implementation of the activity followed the POAC approach (Planning, Organizing, Actuating, Controlling) in a structured manner. Activities included storytelling (using engaging illustrations), screening of age-appropriate educational videos, practical simulations of cough etiquette, and fun, interactive games. These methods were designed to encourage active participation and ensure that children could understand and retain the health messages through enjoyable learning experiences. The results showed a notable improvement in the children's understanding and active involvement in practicing healthy coughing techniques, such as covering their mouths with a tissue or the inside of their elbows when coughing. Visual education combined with hands-on practice proved to be highly effective in conveying health messages to young children. The teachers responded positively to the program, emphasizing that the approach used was appropriate and should be widely implemented in other early childhood education institutions. They recognized it as a valuable promotive effort and a long-term health investment for children, laying the groundwork for healthier habits and environments in the future.